Relationship between emotional intelligence and prenatal attachment levels of women with healthy and high-risk pregnancies - Mecdi Kaydırak, Meltem; Küçük Yüceyurt, Nil; Ertürk, Zuhal; Oskay, Ümran (The European Research Journal, 2023)
Objectives: Emotional intelligence enables pregnant women to effectively cope with environmental effects and stressors in a dynamic and changing process. This research was planned for evaluating the relationship between emotional intelligence and prenatal attachment levels of women with healthy and high-risk pregnancies. Methods: Based on the descriptive research design and regression analysis, the research was performed with the participation of 281 pregnant women. Research data were collected through Information Form, Emotional Intelligence Self-Evaluation Scale (EISES) and Prenatal Attachment Inventory (PAI). Results: As per means of scores obtained from the EISES and PAI by women with healthy (133.34 ± 32.30) and high-risk (126.81 ± 35.80) pregnancies, it was found that pregnant women had high levels of emotional intelligence and medium levels of prenatal attachment. Based on research variables, there were no statistically significant differences in means of scores obtained from the Scale and the Inventory by women with healthy and high-risk pregnancies (p > 0.05). It was found that women who voluntarily got pregnant had higher prenatal attachment levels and this difference was statistically significant (x2= 102.81, p < 0.001). It was identified that there was no statistically significant difference in means of scores obtained by pregnant women from the EISES ans PAI (r= -0.060, p = 0.318). Conclusions: It was found that there was no statistically significant difference in prenatal attachment levels of women with healthy and high-risk pregnancies and their prenatal attachment levels had no statistically significant association with their emotional intelligence levels.